Is Competition Only One Click Away? The Digital Markets Act Impact on Google Maps - Louis-Daniel Pape; Michelangelo Rossi (CESifo GmbH, 2024)
This paper examines the impact of the Digital Markets Act (DMA) on consumer behavior, focusing on changes in Google's search result presentation in the European Union (EU). Specifically, it investigates the effects of Google's removal of clickable maps in search results, a modification implemented in January 2024. This change forces users to perform additional searches to access Google Maps or alternative mapping services, thus increasing search costs. Using a difference-in-differences approach, we compare Google search volumes from EU to non-EU countries before and after the implementation of the DMA. By eliminating Google Maps' advantage of being only one click away from Google Search users, we find that EU consumers search significantly more for online mapping services. We measure a 25% and 18% increase in Google's search volume for the query terms maps and google maps, resulting in an excess of 34,407,000 and 8,901,000 searches over six months, respectively. This search increase suggests potential exposure to alternative mapping services. However, searches for services like apple maps and bing maps also rose, but not as significantly. Moreover, traffic data shows a non-significant decrease in visits to Google Maps, suggesting minimal migration to alternative services. These findings indicate that removing Google's one-click advantage can lead to higher search costs for users without significantly boosting the discovery or adoption of alternative mapping services in the short run.
Keywords: L41; L86; K21; 330; self-preferencing; online mapping services; Google Maps; Google Search; Digital Markets Act